2017
DOI: 10.18632/oncotarget.21480
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1 overexpression predicting gastric carcinogenesis, subsequent progression and prognosis: a meta and bioinformatic analysis

Abstract: DNMT1 is important in maintaining DNA methylation, and participates in the oncogenesis via up- or down-regulation leading to hyper-methylation or hypo-methylation. In the meta and bioinformatic analysis, we found that DNMT1 expression was higher in gastric cancer, compared with normal (p < 0.00001), para-cancerous (p = 0.0004) and dysplasia (p < 0.00001) tissues. DNMT1 up-regulation was associated with gender (OR = 2.27, p = 0.006), differentiation (OR = 0.21, p = 0.01) and TNM stage (OR = 0.31, p = 0.0005). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
2
9
0
1
Order By: Relevance
“…When the aberrantly methylated occurs in the mammalian genome, DNMT1 will be transcribed in the nucleus with the expression gradually enhanced, promoting the advancement of DNA methylation and the procession of tumors[7]. Previously, we illustrated that the expression of DNMT1 was significantly higher in GC tissues than in non-GC tissues by meta-analysis[8]. Simultaneously, several studies have also revealed that DNMT1 was strongly expressed in GC and CRC[9,10], suggesting that DNMT1 could be a potential biomarker in screening of GI cancer.…”
Section: Introductionmentioning
confidence: 99%
“…When the aberrantly methylated occurs in the mammalian genome, DNMT1 will be transcribed in the nucleus with the expression gradually enhanced, promoting the advancement of DNA methylation and the procession of tumors[7]. Previously, we illustrated that the expression of DNMT1 was significantly higher in GC tissues than in non-GC tissues by meta-analysis[8]. Simultaneously, several studies have also revealed that DNMT1 was strongly expressed in GC and CRC[9,10], suggesting that DNMT1 could be a potential biomarker in screening of GI cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Mutze et al found that low DNMT1 expression predicted better OS and clinical response in 127 patients treated with adjuvant therapy [ 83 ], and a comprehensive meta-analysis found that tumor tissues are characterized by high expression levels of DNMT1, with respect to normal, para-cancerous, and dysplastic tissues. Moreover, DNMT1 was found upregulated in stage III and IV patients, associated with GC risk and worse prognosis [ 84 ]. Accordingly, the TCGA molecular classification identified DNMT1 as the most upregulated among all DNMTs in each molecular subgroup [ 41 ], suggesting that it could be a common molecular driver for different pathogenesis patterns.…”
Section: Epigenetics Of Gcmentioning
confidence: 99%
“…Although basic helix-loop-helix transcription factor 38 (TWIST1) expression high was implicated in positive proliferation of gastric cancer cell [47] and DNA methyltransferase 1 (DNMT1) expression was higher in gastric cancer than normal, para-cancerous and dysplasia tissues in the bioinformatic meta-analysis [48]. TWIST expression was suppressed by miR-151a-3p upregulation with miR-539-5p (Figure 2A and 3A) and DNMT1 is also blocked by miR-148a-3p upregulation with miR-185-5p, miR-152-3p, miR-126-3p and miR-140-5p (Figure 2A).…”
Section: H Pylori Infection and Cancermentioning
confidence: 99%